Increasing Racial and Ethnic Diversity in the Nursing Workforce: One Pediatric Hospital's Strategic Approach. Issue 5 (September 2022) - Hinson, Tyonne D.; Brostoff, Marcie; Grossman, Amanda Beit; Ward, Valerie L.; Lind, Kathleen; Wood, Laura J.
Abstract: Background: The 2021 Future of Nursing Report 2020-2030: Charting a Path to Achieve Health Equity recognizes increasing racial and ethnic diversity in nursing as an imperative to achieving health equity. Practice Initiatives: Over a 3-year period, nursing and human resource leaders at Boston Children's Hospital, a tertiary care, 454-bed pediatric academic medical center in Massachusetts, developed, implemented, and evaluated specific strategies to increase racial and ethnic diversity in recruitment and hiring of the nursing workforce. These specific strategies focused on cultivating partnerships, building relationships with candidates, and supporting transition into practice. Results: Significant increases in racial and ethnic diversity recruitment and hiring were achieved over the 3-year period. In 2019, strategies yielded a 6% overall increase in total registered nurse diversity hiring with an 18% increase in new graduate diversity hires over 2018. In total, 16.2% of registered nurse hires for 2019 were racially and ethnically diverse. Subsequent years yielded similar success in the recruitment of diverse registered nurses. Clinical Implications: With the projected growth of racial and ethnic minority populations, nursing and health care leaders must prioritize intentional strategic diversity recruitment and retention actions to address this imperative to advance health equity through the creation of a racially and ethnically diverse nursing workforce. Abstract : Nurse and human resource leaders at Boston Children's Hospital, a tertiary care, 454-bed pediatric academic medical center, developed, implemented, and evaluated strategies to increase racial and ethnic diversity in recruitment and hiring of the nursing workforce. Significant increases in racial and ethnic diversity recruitment and hiring were achieved. These strategies can be helpful for nurses and other health care leaders to advance health equity through the creation of a racially and ethnically diverse nursing workforce.